中国高新技术产业开发区研究及其入世后的对策建议 = On China's hi-tech development zones and development strategics after China's accession to the WTO - 王会勇 Wang, Huiyong (2008)
This thesis gives rather comprehensive and detailed analysis quantitatively as well as qualitatively on the development of 53 national hi-tech zones from 1991 to 2000. The analysis focuses on factors including overall conditions, economic type, new and hi-tech, business scale, etc, of these zones. The thesis analyzes possible impact concerning hi-tech zones.